2010
DOI: 10.1016/j.amepre.2009.08.031
|View full text |Cite
|
Sign up to set email alerts
|

State School Nutrition and Physical Activity Policy Environments and Youth Obesity

Abstract: Background With the epidemic of childhood obesity, there is national interest in state-level school policies related to nutrition and physical activity, policies adopted by states, and relationships to youth obesity. Purpose This study develops a comprehensive state-level approach to characterize the overall obesity prevention policy environment for schools and links the policy environments to youth obesity for each state. Methods Using 2006 School Health Policies and Programs Study (SHPPS) state data, qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 15 publications
(13 reference statements)
2
52
1
1
Order By: Relevance
“…Nanney et al [47] found that Food Service and Nutrition (FSN) policy groupings with the strongest associations to youth obesity are policies which pertained to competitive foods and food service standards. After adjusting for factors, nutrition policies addressing competitive foods in other venues, food service director qualifications, and BMI screening remained positively and significantly related to the odds of obesity in children, as revealed by Riis et al [52].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nanney et al [47] found that Food Service and Nutrition (FSN) policy groupings with the strongest associations to youth obesity are policies which pertained to competitive foods and food service standards. After adjusting for factors, nutrition policies addressing competitive foods in other venues, food service director qualifications, and BMI screening remained positively and significantly related to the odds of obesity in children, as revealed by Riis et al [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies included ages 6–12, and data were then extrapolated which focused on the age of inclusion for this review. The size of sample varied anywhere between 186 students involved in a high school intervention [45], to US student population age 10–17 across 50 states in the US [47]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations